2010
DOI: 10.1111/j.1742-4658.2009.07524.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring enzyme activities under standardized in vivo‐like conditions for systems biology

Abstract: Realistic quantitative models require data from many laboratories. Therefore, standardization of experimental systems and assay conditions is crucial. Moreover, standards should be representative of the in vivo conditions. However, most often, enzyme-kinetic parameters are measured under assay conditions that yield the maximum activity of each enzyme. In practice, this means that the kinetic parameters of different enzymes are measured in different buffers, at different pH values, with different ionic strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
159
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 68 publications
(82 reference statements)
8
159
3
Order By: Relevance
“…This indicates that the adjustment of the glycolytic flux to fermentative conditions is to a large extent determined by changes in the levels of metabolic intermediates and effectors; that is, flux control is primarily at the metabolic level. This finding is consistent with earlier more detailed studies on glycolysis [18][19][20][21][22] . The metabolome data, however, do not provide any insight into the differences in fluxes between the two strains, as there are very small differences in metabolite levels between the different strains, and most differences indicate slightly higher metabolite concentrations in the YSBN2 strain, which has lower fluxes.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…This indicates that the adjustment of the glycolytic flux to fermentative conditions is to a large extent determined by changes in the levels of metabolic intermediates and effectors; that is, flux control is primarily at the metabolic level. This finding is consistent with earlier more detailed studies on glycolysis [18][19][20][21][22] . The metabolome data, however, do not provide any insight into the differences in fluxes between the two strains, as there are very small differences in metabolite levels between the different strains, and most differences indicate slightly higher metabolite concentrations in the YSBN2 strain, which has lower fluxes.…”
Section: Resultssupporting
confidence: 83%
“…In connection with the experiment, we also evaluated a new approach to quantify enzyme activities using assay conditions designed to better represent in vivo-like conditions (where the assay medium is designed to mimic the actual intracellular environment, see Methods and Supplementary Methods), as opposed to the typical approach of using optimal conditions for each enzyme (Fig. 3) 19 . We found that with the in vivo-like assays the range of enzyme activities was in the same order of magnitude as the glycolytic flux, which was not observed using traditional analysis of glycolytic enzyme activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the enzyme activity may be different if analyzed in a standard in vitro buffer compared with a buffer that represents the in vivo situation. van Eunen et al (52) analyzed the kinetic parameters of glycolytic and fermentative enzymes of Saccharomyces cerevisiae in a buffer comprising the composition of the yeast cytosol. They showed that some enzymes had largely different activity in the in vivo buffer compared with the enzyme-specific optimum in vitro buffer (52).…”
Section: Discussionmentioning
confidence: 99%
“…van Eunen et al (52) analyzed the kinetic parameters of glycolytic and fermentative enzymes of Saccharomyces cerevisiae in a buffer comprising the composition of the yeast cytosol. They showed that some enzymes had largely different activity in the in vivo buffer compared with the enzyme-specific optimum in vitro buffer (52). Furthermore, HypT dodecamers are the main species under strong overexpression conditions, whereas small oligomers, as typical for LysR-type transcriptional regulators, prevail in wild-type cells (9).…”
Section: Discussionmentioning
confidence: 99%